Trends and Situation of Housing at Athpahariya Community in Dhankuta - Pokhrel, Rudra Prasad (Kutumbha vani, 2024)
Sanitary housing is one of the basic requirements for healthy living, for safety also included as fundamental right. Housing situation of households and structure reflects the socio economic and cultural identity of people. It is also determined by environmental condition. Athpahariya Rai community is a rare community found especially at Dhankuta. A self-administered structured and unstructured questionnaire in Nepali language was used to obtain information from household head, observation, discussion with key informant are used in this study. Most of the traditional households are in insanitary condition with cattle shed. The structure of household has been slightly changed with improving socio economic status and support of Dhankuta municipality but there is not any significant change in living standard of people with low productivity of land, lack of safe drinking water, low level of literacy etc. Roof is changed from straw to zinc sheet and bamboo wall has been changed into stone and mud wall, there are very few household with concrete structure. Modernity towards shelter is just started in terms of shelter in the study area.